Effects of dietary Bacillus amyloliquefaciens on the growth, immune responses, intestinal microbiota composition and disease resistance of yellow catfish, Pelteobagrus fulvidraco - Xue, Mingyang; Wu, Yeying; Hong, Yizhan; Meng, Yan; Xu, Chen; Jiang, Nan; Li, Yiqun; Liu, Wenzhi; Fan, Yuding; Zhou, Yong (Frontiers in Cellular and Infection Microbiology, 2022)
The influence of dietary probiotic Bacillus amyloliquefaciens on the growth performance, digestive enzyme activity, immune parameters and disease resistance of yellow catfish (Pelteobagrus fulvidraco) was evaluated. Commercial diet (C) or diet containing 106 cfu/g B. amyloliquefaciens (T) was fed for 4 weeks, and final weight (FW), specific growth rate (SGR) and feed conversion ratio (FCR) were improved (p <0.05) in the T group. Dietary B. amyloliquefaciens increased protease and amylase activities in the digestive tract after 2 and 4 weeks, respectively. Respiratory burst (RB), plasma lysozyme (LZM) activity, total antioxidant capacity (T-AOC) and superoxide dismutase (SOD) activity were also elevated (p <0.05). Immune-related genes signal transducer and activator of transcription 1 (STATA-1), immunoglobulin M (IgM) and C-type lectin (CTL) were upregulated (p <0.05), but interleukin-1 β (IL-1β) was not (p >0.05). Intestinal microbiota analysis showed that the community structure was significantly different between the two groups; the relative abundance of Cetobacterium was increased but Plesiomonas was decreased in T. Moreover, challenge tests showed that the resistance of fish fed B. amyloliquefaciens against Aeromonas veronii and Edwardsiella ictaluri was significantly enhanced (p <0.05). In conclusion, dietary supplementation of B. amyloliquefaciens can effectively improve the growth performance, digestive enzyme activity, immune responses, intestinal microbiota composition and disease resistance of yellow catfish.